Utilizing Visual Teaching Materials to Assist Students in Science Subjects Improves Science Process Skills - Cut Roza Maizaliani; Muhibbuddin Muhibbuddin; Muhammad Syukri; Saminan Saminan; Cut Nurmaliah; Evendi Evendi; Fitriana Herliana (Postgraduate, University of Mataram, 2024)
The purpose of this study is to analyze the improvement of student's science process skills with the application of visual gaining knowledge media in science subjects. The research method used is an experiment with a quantitative approach. The research design employed in this study is true experiment. The study's target population were all students at SMP Negeri 11 Banda Aceh, while the instance selected in this research were 56 pupils making use of the non-simple random sampling method by means of proportional sampling. The instrument used was 20 items to measure science process skills with multiple choice diagnostic tests. The outcomes of research on science process skills in the experimental class for each indicator were obtained: observing by 31.76%, classifying by 39.99%, interpreting by 62.31%, predicting by 53.42%, asking questions by 27.27%, formulating hypotheses by 21.74%, designing experiments by 34.95%, using tools and materials by 25.83%, applying concepts by 15.46%, and communicating by 21.72%. The study's findings allow for the conclusion that the highest indicator of students' science process skills is in the interpretation indicator, but the least significant indication is in the communication indicator. Therefore, the implementation of visual learning media in science subjects can have a positive impact on improving students science process skills.